2005
DOI: 10.1515/jpem.2005.18.3.247
|View full text |Cite
|
Sign up to set email alerts
|

Rates of Diabetes Mellitus-Related Complications in a Contemporary Adolescent Cohort

Abstract: In this representative and contemporary cohort of diabetic adolescents the incidence of microvascular diabetes-related complications is quite low.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 45 publications
(13 reference statements)
0
3
0
Order By: Relevance
“…This uncertainty is in part due to studies using varying metrics of GV and with differing glycaemic datasets, rendering comparative analysis problematic (Cameron et al 2010. In the context of paediatric type 1 diabetes, clinical microvascular pathology is relatively rare in patients with good metabolic control (Mohsin et al 2005, Kong et al 2005. On the other hand there is an emerging literature highlighting the relative frequency of neurocognitive and psychological pathology in this younger population (Northam et al 2006, Cameron et al 2007.…”
Section: Introductionmentioning
confidence: 99%
“…This uncertainty is in part due to studies using varying metrics of GV and with differing glycaemic datasets, rendering comparative analysis problematic (Cameron et al 2010. In the context of paediatric type 1 diabetes, clinical microvascular pathology is relatively rare in patients with good metabolic control (Mohsin et al 2005, Kong et al 2005. On the other hand there is an emerging literature highlighting the relative frequency of neurocognitive and psychological pathology in this younger population (Northam et al 2006, Cameron et al 2007.…”
Section: Introductionmentioning
confidence: 99%
“…A more holistic approach has been advocated 1 that also takes into account patient satisfaction of care, costs of care and health‐related quality of life (HRQOL). Using this schema of outcome measures over the last 6 years, we have published data from our diabetes clinic pertaining to clinical outcomes, 2,3 psychological outcomes, 4,5 costs of care 6 and HRQOL 2,7,8 …”
Section: Introductionmentioning
confidence: 99%
“…A similar study by Yoo et al (2004) showed that persistent microalbuminuria and macroalbuminuria were observed in 11.3 and 2.8% of patients with DM1. But the study of Kong et al (2005) on post DCCT showed that prevalence of persistent microalbuminuria was 2% in an adolescent cohort with diabetes duration >5 years due to intensive treatment and the decreased rate of complication. This decreasing trend of microvascular complications was also proved by Mohsin et al (2005) by doing further cross sectional analysis of complications from 1990 to 2002.…”
Section: Discussionmentioning
confidence: 98%